Improved glycine-extracted complement-fixing antigen for human cytomegalovirus. - Kettering, J D (1977)
High-titered, sensitive, and stable complement-fixing antigens for human cytomegalovirus were consistently produced from human diploid fibroblast cells infected at a high multiplicity of virus, harvested after 7 days of incubation, and sonically treated immediately in 0.1 M glycine buffer, pH 9.5.